Influence of Educational Videos on Knowledge and Attitude on Reproduktive Health in Adolescent - Eti Nopyanti; Elfira Sri Futriani; Suliati Suliati; Farida Murtiani; Aninda Dinar Widiantari (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: Reproductive health education is essential to improve knowledge and attitude to grow up and live healthily. Audiovisual media as teaching method is considered as effective way to deliver message and material for health topic in teenager. It was reported that 10-14 years-old adolescent in Jakarta has reached 874,865 people in 2020. High populated of adolescent increased higher-risk sexual behavior. Sexual and reproductive education aims to increase knowledge about the anatomy and physiology of the organs and also improve attitude to avoid high-risk sex behavior.   Objective: We aim to observe the effect of educational videos on the knowledge and attitudes of adolescents about reproductive health. Method: Quasi-experimental research with pre and post-test without control group. Research sample was 100 students of 231 Junior School Jakarta using systematic random sampling. Intervention was educational videos about healthy sex behavior. Result: We found significantly increased average knowledge (15,91 vs 23,24, p= 0,0001) and attitude (34,12 vs 43,26, p= 0,0001) score after the intervention.   Conclusion: There was an significant diffrence of adolescents' knowledge and attitudes about reproductive health after educational video interventions. School and teacher play an active role in reproductive health counseling activities for adolescents with the right media.